The Quality of Life as a Sociological Category – from Theory to Social Research. The Case of Rybnik - Zygmunt, Agata (Political Preferences, 2017)
The aim of the article is to present the quality of life as a category which is used on the basis of social sciences, especially sociology, in the theoretical and empiricalaspect. It describes problems connected with quality of life defining. Complicated genesis, as well as interest in the issue of quality of life of representatives of various disciplines makes it difficult to understand it in an unequivocal way. On the basis of sociology, it has an intersubjective dimension, because the subject of the quality of life in sociological research is the community that is considered in a specific socio-cultural context. Its members express opinions about particular spheres of their own lives, assessing the level of their well-being. An example of sociological research on the quality of life are research carried out in Rybnik. While designing this research, the quality of life was operationalized by selecting indicators that were used in survey questions. The article presents selected results of research on the quality of life of Rybnik, and also draws attention to methodological problems encountered by sociologists investigating this issue. Key words: quality of life, standard of living, sociological research, local community, Rybnik